2009
DOI: 10.1002/cncr.24520
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of factors that contribute to decreased quality of life in Gynecologic Oncology Group ovarian cancer trials

Abstract: BACKGROUND: The objective of this study was to assess which quality‐of‐life (QOL) line items on the Functional Assessment of Cancer Therapy‐Ovarian (FACT‐O) were associated with low QOL in women who were receiving chemotherapy for ovarian cancer. METHODS: Patients with stage III or IV ovarian cancer on Gynecologic Oncology Group Protocols 152 and 172 who underwent primary surgery followed by intravenous paclitaxel and cisplatin completed the FACT‐O. The FACT scale includes the 4 domains of physical, functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 20 publications
5
45
0
3
Order By: Relevance
“…Baseline compliance with questionnaire completion was 95% in this study, which is comparable to that observed in other studies of patients with ovarian cancer [11][12][13][14]. Not unexpectedly, the completion rate dropped off significantly at later time points-especially after 21 cycles of therapy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Baseline compliance with questionnaire completion was 95% in this study, which is comparable to that observed in other studies of patients with ovarian cancer [11][12][13][14]. Not unexpectedly, the completion rate dropped off significantly at later time points-especially after 21 cycles of therapy.…”
Section: Discussionsupporting
confidence: 90%
“…The primary concerns to advanced ovarian cancer patients include alopecia, peripheral neuropathy, pain, neutropenia, fatigue and anxiety, in addition to the effects of their disease on physical and social functioning [19,20]. Evaluating these patient concerns is now considered to be widely advocated for the overall assessment of risks and benefits of new drugs for the treatment of recurrent/relapsed ovarian cancer [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge of improved relative survival after the 5-year point can provide important prognostic information for patients facing survivorship. 24 In this study, patients undergoing primary cytoreductive surgery had drastically improved survival compared with those patients undergoing an alternative primary therapy. Across all stages, relative survival rates at 5 and 10 years were 53% and 42% for those who had surgery and 8% and 6% for those who did not.…”
Section: Discussionmentioning
confidence: 97%
“…Understanding that all women are not equally able to tolerate treatment and providing support during what is often very rigorous treatment may increase treatment effectiveness. A promising line of research is the identification of QOL items that may signal reduced ability to optimally undergo treatment (Gil et al 2007;von Gruenigen et al 2009). …”
Section: Future Research Directionsmentioning
confidence: 99%